2017
DOI: 10.1186/s13104-017-3082-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot investigation on DNA methylation modifications associated with complex posttraumatic symptoms in elderly traumatized in childhood

Abstract: ObjectiveComplex posttraumatic stress disorder (CPTSD) is a newly proposed diagnosis in the International Classification of Diseases-version 11, which is currently intensively investigated. Childhood trauma is regarded as main source of CPTSD symptoms, even in later life. Induction of DNA methylation changes by childhood trauma may contribute to its long-lasting adverse health consequences. The current study analyzed the correlation of genome-wide DNA methylation profiles with complex posttraumatic sequelae in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…46,47 Furthermore, childhood trauma has been reported to increase methylation of the carnosine synthase gene thereby decreasing carnosine synthesis which may contribute to the accelerated biological aging upon becoming adults. 48 There are no reports on whether changes in carnosine synthesis accompany psychological trauma in adults, but it is known that carnosine can exert beneficial effects following physical injury 49,50 and there are also reports of positive effects of carnosine towards glycaemic control and obesity. 51 Animal studies indicate that the dipeptide may suppress anxiety.…”
Section: Carnosine Human Aging and Cognitionmentioning
confidence: 99%
“…46,47 Furthermore, childhood trauma has been reported to increase methylation of the carnosine synthase gene thereby decreasing carnosine synthesis which may contribute to the accelerated biological aging upon becoming adults. 48 There are no reports on whether changes in carnosine synthesis accompany psychological trauma in adults, but it is known that carnosine can exert beneficial effects following physical injury 49,50 and there are also reports of positive effects of carnosine towards glycaemic control and obesity. 51 Animal studies indicate that the dipeptide may suppress anxiety.…”
Section: Carnosine Human Aging and Cognitionmentioning
confidence: 99%
“…It is perhaps interesting to note that carnosine synthesis may be affected by trauma, even in the distant past, which could influence an individual's blood carnosine and acetyl-carnosine levels. In adults subjected to childhood trauma, the carnosine synthase gene showed increased methylation, which would decrease carnosine synthesis [41]. Childhood trauma has been linked to psychopathology, accelerated aging-related DNA methylation [42] and schizophrenia [43].…”
Section: Carnosine and Bloodmentioning
confidence: 99%
“…Recent studies have shown that epigenetic regulation factors such as DNA methylation may modulate gene × environment interactions and impact on neurodevelopment. Environmental factors such as early life stress and childhood maltreatment alter DNA methylation patterns [15][16][17][18][19][20] and potentiate maladaptive behaviours and psychiatric disorders [21][22][23][24][25] . However, relatively few studies have investigated the contribution of epigenetic factors to BPD.…”
Section: Introductionmentioning
confidence: 99%